Timing of exposure and nutritional status affect male response to guava volatiles, a known courtship enhancer of Anastrepha fraterculus - Belliard, Silvina Ahnahi (2021)
Finding ways to improve the sexual competitiveness of laboratory reared males have proven beneficial for the sterile insect technique. Exposure to essential oils enhances male mating success in several species of Tephritidae fruit flies. In Anastrepha fraterculus, males exposed to volatile compounds released by fresh guava fruit exhibit an increased courtship frequency and mating success. Here, we investigated how A. fraterculus male sexual behavior is affected when they are exposed to a commercial guava essential oil and tested its potential to accelerate male sexual maturation. In addition, we addressed the effect of the timing of exposure, and the diet males received on their response to the oil. Guava essential oil was as effective as guava fruit odors as a sexual calling enhancer. Neither the fruit nor the oil had a significant effect on sexual maturation. Guava oil sexual stimulation was only observed when males were exposed after attaining sexual maturation and fed on a low-quality diet. Males fed on high-quality diet showed higher calling levels than males fed on low-quality diet or sugar, irrespectively of guava oil exposure. We found no detrimental consequences of treatment on male starvation resistance. We discuss these results from an applied and ecological perspective.